Creating an Online Scientific Art Exhibit Formatted for People with a Visual Impairment. Issue 2 (3rd April 2017) - Sorrell, Melanie; Norton, Derek; McAdams, Jeff; Winterling, Rachael; Dipple, Kathleen
ABSTRACT: An online exhibit accessible by people with a visual impairment was created to accompany a university library's physical exhibit of microscopic images generated by researchers on campus as "scientific art." This online exhibit consisted of a web page formatted for screen-reading software so that those individuals could hear descriptions of the images and envision the image patterns, shapes, textures, and perhaps colors while learning about the scientific research performed on campus. The library promoted this web page through various outlets to a wide audience to benefit patrons on and off campus. The exhibit was successful, and lessons learned through this project can be applied by other libraries undertaking similar efforts, to navigate problems and improve efficiency in implementing online exhibits for people with a visual impairment.